Compact polar moieties induce lipid-water systems to form discontinuous reverse micellar phase - Kumar, Manoj; Patil, Naganath G.; Choudhury, Chandan Kumar; Roy, Sudip; Ambade, Ashootosh V.; Kumaraswamy, Guruswamy (Soft Matter, 2015)
The role of molecular interactions in governing lipid mesophase organization is of fundamental interest and has technological implications. Herein, we describe an unusual pathway for monoolein/water reorganization from a bicontinuous mesophase to a discontinuous reverse micellar assembly, directed by the inclusion of polar macromolecules. This pathway is very different from those reported earlier, wherein the Fd3m phase formed only upon addition of apolar oils. Experiments and molecular dynamics simulations indicate that hydrophilic ternary additives capable of inducing discontinuous phase formation must (i) interact strongly with the monoolein head group and (ii) have a compact molecular architecture. We present a detailed investigation that contrasts a monoolein-water system containing polyamidoamine (PAMAM) dendrons with one containing their linear analogs. The Fd3m phase forms only on the addition of PAMAM dendrons but not their linear analogs. Thus, the dendritic architecture of PAMAM plays an important role in determining lipid mesophase behavior. Both dendrons and their linear analogs interact strongly with monoolein through their amine groups. However, while linear polymers adsorb and spread on monoolein, dendrons form aggregates that interact with the lipid. Dendrons induce formation of an intermediate reverse hexagonal phase, which subsequently restructures into the Fd3m phase. Finally, we demonstrate that other additives with compact structures that are known to interact with monoolein, such as branched polyethylenimine and polyhedral silsesquioxane cages, also induce the formation of the Fd3m phase.